Mercury tolerance of Penicillium sp isolated from kefir grains - Oliveira, Antonio Ferreira; Florentino, Alexandro Cezar; Sena, Iracirema Silva; Ferreira, Adriana Maciel; Bezerra, Roberto Messias; Carvalho, José Carlos Tavares; Ferreira, Irlon Maciel (Ciência e Natura, 2018)
Inorganic contaminant contamination poses the greatest threat to the environment and human health. It has been recently reported that probiotics protect the body from inorganic contaminant damage by the bioabsorption capacity of its components. Kefir is a beverage obtained through the fermentation metabolized by Lactobacillus and yeasts that aggregate forming the grains of kefir. In order to isolate inorganic contaminant resistant microorganism, the kefir grains were crushed and the supernatant obtained was inoculated in malt-gar medium (2%) and cultured for 120 hours. Occurred formation of halos of growth which were measured every 24 hours. The isolated microorganism was also cultured in liquid medium for five days. The taxonomic analysis revealed to be fungus of the genus Penicillium. The results showed the capacity of mercury bioabsorption by Penicillium sp isolated from kefir. At pH 4.0 this activity did not suffer strong inhibition. Contrary to what was expected there was an increase in biomass when grown in liquid medium which suggests the formation of storage structures of the inorganic contaminant around the cell membrane. These results confirm that kefir contains in its composition microorganisms capable of protecting people who consume it from harmful damages caused by inorganic contaminants.